Vascularized Mini Cooling Channels To Achieve Temperature Uniformity: Battery Thermal Management and Electronic Cooling - Coşkun, Turgay; Çetkin, Erdal; Çetkin, Erdal; Coşkun, Turgay (MIM RESEARCH GROUP, 2023)
Here we propose to use of distinct vascularized plates to be used in the applications of battery thermal management and electronic cooling. The temperatures of battery cells increase during charge and discharge; and elevated temperature values in them accelerated degradation and even may trigger battery fire because of the thermal runaway. Therefore, thermal management system is a necessity for battery packs to increase the battery performance and diminish the risk factors in the electric vehicles. Generally, high amount of heat is released in the high capacity (>15 Ah) cells in short time interval under fast charge/discharge conditions; thus, thermal management of the battery system can be achieved with liquid cooling in that situation. A silicon heater system which represents the thermal behavior of a battery cell is manufactured based on the literature and it is used in experiments. Such a method has not proposed up to now in the literature, so the study may be creating a new experimental procedure for future studies without the risk of battery fire/degradation to uncover even extreme conditions experimentally. Electronic cooling is also in prime importance due to enhanced computing requirement of current systems, and vascularized plates can solve the hot spot problems occurring with decreased energy consumption. According to the results, the cooling capacity of the vascularized plates are calculated as 20W, and a battery cell can be kept within its optimal operating temperature range when the heat loads up to 30W. Also, the temperature uniformity along the surface of mimic of the battery is satisfied by vascularized plates.
Keywords: Battery Cell Mimicking Structures; Cooling System; Silicon Heater; Thermal Management